Hybrid nanocrystalline TiO2 solar cells with a fluorene-thiophene copolymer as a sensitizer and hole conductor - Ravirajan, P.; Haque, S.A.; Durrant, J.R.; Poplavskyy, S.A.; Bradley, D.D.C.; Nelson, J. (Elsevier B.V., 2004)
The charge separation and photovoltaic properties of TiO2/polymer hybrid structures was reported. As such, efficient photoinduced charge transfer was observed from a fluorene-thiophene copolymer to the TiO2 film, while interfacial recombination was relatively slow. As a result, effective penetration of the polymer into porous nanocrystalline films was achieved to films of around 100 nm thickness.